2015
DOI: 10.1021/acs.langmuir.5b00853
|View full text |Cite
|
Sign up to set email alerts
|

Versatile (Bio)Functionalization of Bromo-Terminated Phosphonate-Modified Porous Aluminum Oxide

Abstract: Porous aluminum oxide (PAO) is a nanoporous material used for various (bio)technological applications, and tailoring its surface properties via covalent modification is a way to expand and refine its application. Specific and complex chemical modification of the PAO surface requires a stepwise approach in which a secondary reaction on a stable initial modification is necessary to achieve the desired terminal molecular architecture and reactivity. We here show that the straightforward initial modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
(69 reference statements)
0
18
1
Order By: Relevance
“…Interestingly, higher immobilization densities were obtained when alkene‐modified oligonucleotides were immobilized onto the thiolated surfaces. This shows that the location of the thiol moieties influences the TEC reaction, and this contrasts with the findings of Tingaut et al and Debrassi et al, who found surface‐bound alkenes to be significantly preferable over surface‐bound thiols for TEC purposes.…”
Section: Thiol‐ene Click Reactionscontrasting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, higher immobilization densities were obtained when alkene‐modified oligonucleotides were immobilized onto the thiolated surfaces. This shows that the location of the thiol moieties influences the TEC reaction, and this contrasts with the findings of Tingaut et al and Debrassi et al, who found surface‐bound alkenes to be significantly preferable over surface‐bound thiols for TEC purposes.…”
Section: Thiol‐ene Click Reactionscontrasting
confidence: 92%
“…This low reaction rate was attributed to the homopolymerization of allylbutyrate in the reaction medium or the poor accessibility of the thiol moieties on the surface. Such a reactivity pattern—surface‐bound alkenes reacting much faster in TEC chemistry than surface‐bound thiols—was also observed by Debrassi et al for TEC chemistry on porous aluminum oxide . In their third approach, Tingaut et al first reacted vinyltrimethoxy­silane with methylthioglycolate using click chemistry, followed by grafting of the resulting silane product onto the cellulose surface with high modification rates.…”
Section: Thiol‐ene Click Reactionsmentioning
confidence: 62%
See 1 more Smart Citation
“…58 As a result, materials derived from SB or CB are considered as biomimetic. 1 Their biomimetic nature along with their excellent antifouling characteristics make them interesting for a wide range of applications, 13,59 such as biosensing, [60][61] drug delivery, 12,62 filtration, 51,[63][64] as well as for antibacterial 65 and marine coatings. 15,66 A fundamental difference between SB and CB is that CB-based materials can be directly functionalized (mostly via EDC/NHS chemistry to attach antibodies, see below), and are therefore often used for biosensing applications.…”
Section: Phosphocholinementioning
confidence: 99%
“…For instance, as shown in chapter 3, the beads can be functionalized by substitution of the terminal halogen atom by a primary amine, which allows for the incorporation of a functional groups such as alkenes or alkynes. 62 Difficulties may arise when organic solvents need to be used (as was needed to dissolve the fluorinated amino compound, see chapter 3, Scheme 3.1), because the zwitterionic polymer-coated beads tend to aggregate under these conditions. Converting the halogen atom into an azide moiety is therefore preferred: this reaction is performed in PBS in which the zwitterionic beads are most easily handled.…”
Section: Romantic Beadsmentioning
confidence: 99%